The Role of the United States Dollar as an International Currency in the Second Half of the 20th Century - Pavelec, Boris; Johnson, Zdenka, 1983-; Chalupecký, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
This thesis maps the role of the U.S. dollar as an international currency with a main focus on the second half of the 20th century and the role of dollar in the world economy. The thesis spans from the end of the Second World War to the eve of the last global financial crisis. The thesis documents, how dollar became the leading international currency during the Bretton Woods system era. Although the inner conflicts led to breakup of the system, dollar remained the most important currency. Despite many attempts, a successful reform of the international monetary system never happened since then. In the last 30 years, the uncoordinated U.S. monetary policy led to rapid growth of imbalances in the world economy and consequently to the 2007/08 Financial crisis. The thesis shows that the viable reform can build on the original plan of John M. Keynes, which prepared for the Bretton Woods conference.
Vedoucí práce: Zdenka Johnson
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses